2015
DOI: 10.1165/rcmb.2014-0141oc
|View full text |Cite
|
Sign up to set email alerts
|

CD38 Mediates Angiotensin II–Induced Intracellular Ca2+ Release in Rat Pulmonary Arterial Smooth Muscle Cells

Abstract: inhibitors apocynin and diphenyleneiodonium, the NOX2-specific inhibitor gp91ds-tat, and the scavenger of reactive oxygen species (ROS) tempol. These results provide the first evidence that Ang II activates CD38-dependent Ca 21 release via the NOX2-ROS pathway in PASMCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 50 publications
3
23
0
Order By: Relevance
“…We also showed that ER Ca 2+ mobilization may be important because dantrolene, which blocks ryanodine receptor, reduced contraction only in Nox5 mice. Previous studies in coronary arterial myocytes and pulmonary arterial smooth muscle cells demonstrated that ryanodine receptor/Ca 2+ regulation involves ER‐associated Nox (2 and 4)‐derived ROS 43, 44. Our findings are supportive of this association, although the exact role of Nox5 in ER function warrants further investigation.…”
Section: Discussionsupporting
confidence: 83%
“…We also showed that ER Ca 2+ mobilization may be important because dantrolene, which blocks ryanodine receptor, reduced contraction only in Nox5 mice. Previous studies in coronary arterial myocytes and pulmonary arterial smooth muscle cells demonstrated that ryanodine receptor/Ca 2+ regulation involves ER‐associated Nox (2 and 4)‐derived ROS 43, 44. Our findings are supportive of this association, although the exact role of Nox5 in ER function warrants further investigation.…”
Section: Discussionsupporting
confidence: 83%
“…We have recently characterized the expression of CD38 and the CD38-dependent Ca 2+ response in PASMCs. We found that CD38 is highly expressed in PAs compared to other systemic arteries [47,48]. It plays important roles in Ca 2+ response activated by agonists, including angiotensin II, endothelin-1 and integrin-ligands through cADPR and NAADP-dependent mechanisms [47][48][49].…”
Section: +mentioning
confidence: 87%
“…We found that CD38 is highly expressed in PAs compared to other systemic arteries [47,48]. It plays important roles in Ca 2+ response activated by agonists, including angiotensin II, endothelin-1 and integrin-ligands through cADPR and NAADP-dependent mechanisms [47][48][49]. In particular, Ang II elicits CD38-dependent Ca 2+ release in PASMCs via PKC-dependent production of reactive oxygen species from NADPH oxidase 2 [48].…”
Section: +mentioning
confidence: 90%
See 1 more Smart Citation
“…Aldehyde dehydrogenase 1 family-member A1 (Aldh1a1), aldolase C-fructose-bisphosphate (Aldoc), and CD38 are oxygen-related enzymes, and Vegfa, Tgb2, and Ctgf are oxygen-related receptor ligands [21]. CD38 has been recently implicated to regulate Ca 2+ signaling in response to ROS generation in pulmonary arterial SMCs [74]. Therefore, it would be interesting to examine the importance of CD38 in the DA.…”
Section: Response To Oxygenmentioning
confidence: 99%